Research on key "acupoint" mining technology for special information system - ZOU Zilong, WANG Junlin, AN Shujie, LYU Changyuan, YU Minggang, NIU Yanjie (Zhihui kongzhi yu fangzhen)
Special information system is a complex information system with specific architecture, clear functional positioning, and diverse components and relationships among elements, and the key point refers to the node or component element that plays a key role in the system, and the damage of "acupuncture point" will have a huge impact on the function and utility of the whole system. It is of great scientific value and practical application significance to study how to excavate the key points of the system. In this paper, the complex network theory is used to analyze the network characteristics of special information system. On this basis, from the two dimensions of "static" and "dynamic", five indexes are proposed respectively, namely, transcendence, clustering coefficient, eigenvector centrality, network elasticity and network destruction resistance, which are used to evaluate the importance of each node. Next, YAANP decision software is used to determine the weight of each index, and then a key "acupoint" mining method for special information system is proposed. Finally, taking the special information system under the background of urban unmanned attack operation as an example, the scientific and reasonable of the proposed method is verified.